Implementing Human Resource Strategies for Enhancing Employee Performance in the Livestock Sector: A Case Study of Talent Retention and Development - Azzahra, Adelia (Politeknik Siber Cerdika Internasional, 2024)
This study examines the implementation of human resource (HR) strategies aimed at enhancing employee performance, talent retention, and development in the livestock sector. Using a qualitative case study approach, data were collected from interviews with HR managers, supervisors, and employees, supplemented by employee questionnaires and direct observations. Findings reveal that HR strategies focusing on professional development—such as structured training programs and career advancement opportunities—significantly improve employee performance and job satisfaction. Farms implementing these practices experienced a retention rate increase from 60% to 85%, leading to greater workforce stability and reduced recruitment costs. Additionally, employee productivity improved by 30%, as workers gained technical expertise and adaptability to technological advancements in livestock management. owever, financial constraints and limited access to modern HR technology pose challenges to broader implementation. Many farms struggle to allocate resources for sustained HR initiatives, and rural operations face difficulties in integrating digital HR tools for training and performance tracking. The impact of these findings is significant. Continuous investment in employee development is essential for maintaining productivity and competitiveness, particularly in industries undergoing rapid technological shifts. Policymakers and industry leaders should explore financial support mechanisms, technology-driven HR solutions, and incentives for employee upskilling. This study contributes to HR literature by providing sector-specific insights and practical recommendations for strengthening HR practices in agriculture and related industries.